Penentuan Prioritas Penanganan Genangan di Kecamatan Lembursitu, Kota Sukabumi - Bagya Trirahmani, Anggia; Eka Wardhani; Didin Agustian Permadi; Etih Hartati (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Lembursitu Subdistrict is one of the areas in Sukabumi City that often experiences flooding, especially during the high-intensity rainy season. This study aims to determine the priority of flood management in six affected locations spread across four villages. Priority assessment was carried out using a weighting method based on six parameters listed in the Minister of Public Works Regulation No. 12 of 2014, namely flood height, flood area, flood duration, flood frequency, economic losses, social and government facility disruptions, transportation losses and disruptions, housing losses, and private property losses. The research data was obtained through field surveys, community interviews, and secondary data from relevant agencies in Sukabumi City. The weighting results showed that the location with the highest priority for handling was L6 (Jl Raya Palabuhan II) with a score of 297.5, followed by L5 (Jl Merdeka) and L1 (Jl Merdeka). These three locations have a major impact on social, economic, transportation, and public service facility activities. These findings provide a basis for local governments to determine more effective flood management strategies, particularly through increasing drainage capacity, channel normalization, and the implementation of a sustainable eco-drainage-based flood control system.